Shifts Between and Among Populations of Wheat Rhizosphere Pseudomonas, Streptomyces and Phyllobacterium Suggest Consistent Phosphate Mobilization at Different Wheat Growth Stages Under Abiotic Stress - Breitkreuz, Claudia; Buscot, François; Tarkka, Mika; Reitz, Thomas (Frontiers in Microbiology, 2020)
Climate change models predict more frequent and prolonged drought events in Central Europe, which will exert extraordinary pressure on agroecosystems. One of the consequences is drought-related nutrient limitations for crops negatively affecting agricultural productivity. These effects can be mitigated by beneficial plant growth promoting rhizobacteria. In this study, we investigated the potential of cultivable bacterial species for phosphate solubilization in the rhizosphere of winter wheat at two relevant growth stages - stem elongation and grain filling stages. Rhizosphere samples were collected in the Global Change Experimental Facility in Central Germany, which comprises plots with conventional and organic farming systems under ambient and future climate. Phosphate solubilizing bacteria were selectively isolated on Pikovskaya medium, phylogenetically classified by 16S rRNA sequencing, and tested for in vitro mineral phosphate solubilization and drought tolerance using plate assays. The culture isolates were dominated by members of the genera Phyllobacterium, Pseudomonas and Streptomyces. Cultivation-derived species richness and abundance of dominant taxa, especially within the genera Phyllobacterium and Pseudomonas, as well as composition of Pseudomonas species were affected by wheat growth stage. Pseudomonas was found to be more abundant at stem elongation than at grain filling, while for Phyllobacterium the opposite pattern was observed. The abundance of Streptomyces isolates remained stable throughout the studied growth stages. The temporal shifts in the cultivable fraction of the community along with considerable P solubilization potentials of Phyllobacterium and Pseudomonas species suggest functional redundancy between and among genera at different wheat growth stages. Phosphate-solubilizing Phyllobacterium species were assigned to Phyllobacterium ifriqiyense and Phyllobacterium sophorae. It is the first time that phosphate-solubilization potential is described for these species. Since Phyllobacterium species showed the highest drought tolerance along all isolates, they may play an increasingly important role in phosphate solubilization in a future dryer climate.